Fumarate hydratase (FH) deficiency in uterine leiomyomas: recognition by histological features versus blind immunoscreening - Siegler, Lisa; Erber, Ramona; Burghaus, Stefanie; Brodkorb, Tobias; Wachter, David; Wilkinson, Nafisa; Bolton, James; Stringfellow, Helen; Haller, Florian; Beckmann, Matthias; Hartmann, Arndt; Agaimy, Abbas (Virchows Archiv, 2018)
Hereditary leiomyomatosis and renal cell carcinoma (HLRCC) syndrome is a rare autosomal dominant disease caused by germline mutations in the fumarate hydratase (FH) gene. Affected individuals develop cutaneous and uterine leiomyomas and aggressive RCC. To date, only few publications described the frequency and morphology of FH-deficient uterine leiomyomas. We reviewed 22 cases collected over 8 years from routine and consultation files based on distinctive histological features. In addition, we screened 580 consecutive uterine leiomyomas from 484 patients, 23 extra-uterine and 8 uterine leiomyosarcomas, and 6 leiomyomas with bizarre nuclei for FH loss using immunohistochemistry (IHC) on tissue microarrays (TMAs). All 22 FH-deficient cases were suspected on H&E sections and confirmed by FH IHC. Patients' ages ranged from 25 to 70 years (median 36). Seventeen patients had multiple nodules (2-14) measuring up to 11.8 cm. None of the patients had stigmata or family history of the HLRCC syndrome. Histologically, all FH-deficient tumors showed consistent and reproducible features as reported previously. FH loss was detected in 2/534 evaluable leiomyomas (0.4%), but in none of leiomyosarcomas. Two of six leiomyomas with bizarre nuclei were FH-deficient. FH-deficient uterine leiomyomas are rare in routine material (= 0.4%). They can be reliably identified or suspected by consistent morphological features. Our data showed predictive morphology to be superior to blind IHC screening for detecting them. The relationship of FH-deficient uterine smooth muscle tumors to the HLRCC syndrome needs further clarification.
EVALuna2:33962